2022
DOI: 10.3390/life12040573
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Bond Formation between Aminoacyl-Minihelices by a Scaffold Derived from the Peptidyl Transferase Center

Abstract: The peptidyl transferase center (PTC) in the ribosome is composed of two symmetrically arranged tRNA-like units that contribute to peptide bond formation. We prepared units of the PTC components with putative tRNA-like structure and attempted to obtain peptide bond formation between aminoacyl-minihelices (primordial tRNAs, the structures composed of a coaxial stack of the acceptor stem on the T-stem of tRNA). One of the components of the PTC, P1c2UGGU (74-mer), formed a dimer and a peptide bond was formed betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 49 publications
(86 reference statements)
0
24
0
Order By: Relevance
“…Recently, it was found that certain combinations of the aforementioned segments are capable of mediating peptide bond formation [ 27 ] using chemically synthesized P- and A-site analogs [ 28 ]. Furthermore, we have shown that a piece of RNA formed a dimer and that a peptide bond was formed between two aminoacyl minihelices (primordial tRNAs) tethered by the dimeric structure [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was found that certain combinations of the aforementioned segments are capable of mediating peptide bond formation [ 27 ] using chemically synthesized P- and A-site analogs [ 28 ]. Furthermore, we have shown that a piece of RNA formed a dimer and that a peptide bond was formed between two aminoacyl minihelices (primordial tRNAs) tethered by the dimeric structure [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tamura's team eventually achieved its own success, also detecting the dipeptide with mass spectrometry 3 . "Mai and Kentaro were patient and responsive, and finally, we won a big win," says Tamura.…”
Section: Next Stepsmentioning
confidence: 99%
“…And the lab's achievements in the past two years -creating a primitive RNA machine that can link two amino acids together 1,2 -have created a ripple of excitement. A group in Japan, working separately and led by molecular biologist Koji Tamura at the Tokyo University of Science, has succeeded in creating a similar, functional protoribosome 3 . "It's strongly supportive of Ada's protoribosome idea," says Paul Schimmel, a biochemist at Scripps Research in La Jolla, California.…”
mentioning
confidence: 99%
“…RNA could also have helped peptide synthesis (Figure 3 (iii)), as short RNAs with the non‐canonical bases conserved in ribosomes and tRNAs reportedly supported the elongation of peptides covalently bound to themselves (Müller et al, 2022). The proto‐ribosomes reconstructed from the core structures of modern ribosomes were able to catalyze peptide bond formation between amino acids charged on short tRNA models (Bose et al, 2022; Kawabata et al, 2022; Xu & Wang, 2021). Thus, RNA might first have been stabilized/supported by prebiotic peptides synthesized non‐enzymatically and then evolved to synthesize simple peptides more efficiently for its own purposes (Figure 3 (iv)).…”
Section: Evolutionary Scenarios From Simple Peptides To Folded Proteinsmentioning
confidence: 99%